Ultrasound-assisted natural deep eutectic solvent extraction of phenolic compounds from apple pomace. Issue 2 (22nd January 2023) - Deniz, Selin; Ünlü, Ayşe Ezgi; Takaç, Serpil
ABSTRACT: In this study, an environmentally friendly and efficient method based on natural deep eutectic solvent (NADES) in combination with ultrasound-assisted extraction was used for the recovery of phenolic compounds from apple pomace. Acidic, alkaline, sugar-based and polyol-based NADESs were examined for extraction of total phenolic content from apple pomace under different conditions.NADES type, biomass percentage, extraction temperature, extraction time and water content were the testing parameters. NADES type and water content of the solvent were the most important parameters that affected the extraction yield. The most effective NADESs were sugar-based NADESs, which were followed by acidic NADESs. Up to 9.47 mgGAE /gapple pomace was recovered from apple pomace with glucose:sucrose:water. The highest total flavonoid content was obtained with choline chloride:urea as 17.30 mgEPE /gapple pomace . On the other hand, NADES composed of choline chloride – lactic acid was found to exhibit a significant antioxidant activity. The novelty of this article is the investigation of acidic, alkaline, sugar-based and polyol-based NADESs in the recovery of phenolic compounds from apple pomace using ultrasound-assisted extraction, for the first time in the literature. The antioxidant activity of extracts were also explained in combination with that of NADESs.